Planning and development of tourist destination in Batam as an industrial city - Syailendra Reza Irwansyah Rezeki; I Wayan Thariqy Kawakibi Pristiwasa (Jurnal Pariwisata Pesona, 2026)
Tourism plays an essential role in enhancing a city’s attractiveness and economic value. However, in Indonesia including Batam City tourism development is often hindered by the dominance of the industrial sector and the lack of sustainable planning. Batam, known as a free-trade and industrial area, also possesses vast potential in marine, cultural, and culinary tourism that remains underutilized.This study aims to describe the planning and development of Batam’s tourism destinations to enable coexistence with the industrial sector. The research applies a qualitative descriptive approach grounded in post-positivism, utilizing literature reviews, government documents, and previous studies analyzed through the SWOT framework.The results indicate that Batam’s tourism strategy should focus on four key areas: strengthening local cultural identity, implementing professional destination management, optimizing digital promotion via social media, and fostering collaboration among government, communities, and industry players. The sustainability of Batam’s tourism depends on balancing industrial growth and environmental preservation.This research contributes to the concept of a sustainable industry-based tourism city and provides policy recommendations for local governments and tourism stakeholders.